Antioxidant Properties of Caffeic acid Phenethyl Ester and 4‐Vinylcatechol in Stripped Soybean Oil. Issue 1 (7th December 2015) - Jia, Cai‐Hua; Wang, Xiang‐Yu; Qi, Jin‐Feng; Hong, Soon‐Taek; Lee, Ki‐Teak
Abstract: Caffeic acid was used to synthesize 4‐vinylcatechol (4‐VC) by thermal decarboxylation and to prepare caffeic acid phenethyl ester (CAPE) by esterification reaction. The identities of synthesized products were confirmed by 1 H NMR. Antioxidative activities of 4‐VC and CAPE were compared with α‐tocopherol and BHT in stripped soybean oil at 60 °C under the dark. To evaluate the degrees of oxidation at different concentrations and combinations, peroxide value (PV) and 1 H NMR were performed. From the results of PV, the formation of primary oxidation products (i.e., hydroperoxides) in stripped soybean oil containing 200 ppm CAPE was the slowest. The relative oxidation degree of 200 ppm CAPE (9.5%) was lower than other samples on 9 d. Similar results were obtained by 1 H NMR analysis. After 15 d of storage, levels of conjugated diene forms and aldehydes of 200 ppm CAPE sample (57.3 and 0.9 mmol/mol oil) were also lower than other treatments. In addition, 4‐VC and α‐tocopherol were found to have a synergistic antioxidant effect.